Physiological Functions of FBW7 in Metabolism - Zhang, Jianmei; Kong, De-huan; Huang, Xiaocheng; Yu, Rongbo; Yang, Yachao (Hormone and Metabolic Research, 2022)
FBW7 is the recognition subunit of the SCF (Skp1-Cullin1-F-box proteins) E3 ubiquitin ligase complex, and it determines the specificity of the SCF substrate. SCFFBW7 is a recognized tumor suppressor because of its ability to degrade many proto-oncogenic substrates. Recent studies have shown that FBW7 plays a key role in metabolism by targeting the degradation of critical regulators involved in cellular metabolism in a ubiquitin-dependent manner. Here, we review recent studies, which highlight the important role of FBW7 in metabolism.
Keywords: FBW7; glucose metabolism; metabolic syndrome; lipid metabolism; obesity